Heterostructured Zn-2MI@V-COF-1@MWCNTs based electrochemical sensor for the sensitive simultaneous detection of ethyl paraben, diclofenac and epinephrine - Antonia Trisha Zac R; Yao-An Tsai; Chih-Ling Yeh; Hui-Ling Lee (Talanta Open)
Rational designing of practical and cost-effective electrochemical sensor with simultaneous sensing of ethyl paraben (EPB), diclofenac (DIC), and epinephrine (EPN) remains a challenging aspect. With a motive to solve this concern, a low-cost screen printed electrodes (SPCE) sensor with a novel hybrid Zn-2MI@V-COF-1@MWCNTs modifications was put forward. In this work, an octahedral imidazole based metal organic frameworks (Zn-2MI) is combined with a two-dimensional vinylene based covalent organic frameworks (V-COF-1) to form (Zn-MOF@V-COF-1) through a simple room temperature synthesis. This hybrid is further integrated with multi-walled carbon nanotubes (MWCNTs) for enhanced analyte detection. The structural and crystalline nature of the hybrid materials was analysed using PXRD, SEM, and TEM. The material exhibits ideal porosity and a large electroactive area with multiple adsorption sites, resulting in effective, sensitive detection towards EPN, DIC, and EPB. The sensor achieves low detection limits of 0.05 µM for DIC and EPN and 0.5 µM for EPB. Real samples analysis including chili powder, liquid sweetener and energy drink are conducted using differential pulse voltammetry using satisfactory results ranging recovery rates from 81.54 to 105.8 %. These excellent performance outcomes, attributes to the synergistic effect and the presence of multiple active sites elucidates that novel Zn-2MI@V-COF-1@MWCNTs/SPCE are reliable sensors that offers quick screening, cost effective, sensitive, and allow simultaneous detection of harmful analytes in complex matrices.